Spread of X-chromosome inactivation into autosomal regions in patients with unbalanced X-autosome translocations and its phenotypic effects - Favilla, Bianca Pereira; Meloni, Vera Ayres; Perez, Ana Beatriz; Moretti-Ferreira, Danilo [UNESP]; Souza, Deise Helena de [UNESP]; Bellucco, Fernanda Teixeira; Melaragno, Maria Isabel (Wiley-Blackwell, 2021)
Patients with unbalanced X-autosome translocations are rare and usually present a skewed X-chromosome inactivation (XCI) pattern, with the derivative chromosome being preferentially inactivated, and with a possible spread of XCI into the autosomal regions attached to it, which can inactivate autosomal genes and affect the patients' phenotype. We describe three patients carrying different unbalanced X-autosome translocations, confirmed by G-banding karyotype and array techniques. We analyzed their XCI pattern and inactivation spread into autosomal regions, through HUMARA, ZDHHC15 gene assay and the novel 5-ethynyl-2 '-deoxyuridine (EdU) incorporation assay, and identified an extremely skewed XCI pattern toward the derivative chromosomes for all the patients, and a variable pattern of late-replication on the autosomal regions of the derivative chromosomes. All patients showed phenotypical overlap with patients presenting deletions of the autosomal late-replicating regions, suggesting that the inactivation of autosomal segments may be responsible for their phenotype. Our data highlight the importance of the XCI spread into autosomal regions for establishing the clinical picture in patients carrying unbalanced X-autosome translocations, and the incorporation of EdU as a novel and precise tool to evaluate the inactivation status in such patients.
Keywords: inactivation spread; late replication; X chromosome; X‐ autosome translocation; chromosome inactivation